Review of measurement methods for hearing protector attenuation - Selamat, Atiqah; Razali, Ailin (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2019)
The attenuation degree labelled on hearing protectors is based on internationally set standards. The attenu- ation is measurement in laboratories using methodology of real-ear attenuation at threshold (REAT), microphone in-real ear (MIRE) and acoustics test feature (ATF). The measured attenuation gap from the actual workplace is a problematic predicament. The conceptual review of how far these methods affect the gap could embark future researches. Therefore, a conceptual review of the conducted methodologies according to standards for attenuation which include Noise Reduction Rating (NRR) and Single Number Rating (SNR) are discussed in this paper. 23 papers from ProQuest, EBSCOhost and Google Scholar databases are chronologically reviewed. Summarily, the improved attenuation measurement methods will help close the gap between laboratory data and field performance and sub- sequently will better prevent Noise-Induced Hearing Loss. Most of the latest findings after year 2010 were in agree- ment with the studies in 2000 to 2009.